Heat-conducting insulating electromagnetic shielding composite material as well as preparation method and application thereof
By evenly dispersing multi-walled carbon nanotubes in a Kevlar 1414 matrix and achieving orderly orientation, the problem of insufficient thermal conductivity in the Kevlar 1414 matrix was solved, and a composite material with high thermal conductivity and excellent electromagnetic shielding properties was prepared, which is suitable for heat dissipation of highly integrated electronic devices.
Patent Information
- Application Number
- CN202510915213.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-03
- Publication Date
- 2025-10-17
AI Technical Summary
In the existing technology, the interfacial thermal resistance and disordered distribution between the nanometer size and the polymer matrix result in insufficient thermal conductivity in the Kevlar 1414 matrix, which cannot meet the efficient heat dissipation requirements of highly integrated electronic devices.
By uniformly dispersing multi-walled carbon nanotubes in a Kevlar 1414 matrix and using the π-π anchoring effect to achieve orderly orientation of the carbon nanotubes and the matrix, a high thermal conductivity composite material is formed.
It achieves high thermal conductivity, good processability, high temperature resistance, flexibility, insulation and electromagnetic shielding performance, and is suitable for the heat dissipation needs of highly integrated, high-power electronic devices. The in-plane thermal conductivity is increased to 9.6W/m·K~23.8W/m·K, the electromagnetic shielding efficiency reaches 60%, and the sheet resistance reaches 4.51KΩ/sq.
Smart Images

Figure CN120795617A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application belongs to the technical field of thermal management, and particularly relates to a heat-conducting, insulating and electromagnetic shielding composite material and a preparation method and application thereof. BACKGROUND
[0002] In modern electronic and semiconductor technology, the integration level is increasingly high, and the power density is also increasing, so efficient thermal management technology has become the key to maintaining the performance and service life of equipment, and therefore higher requirements are put forward for the related thermal management system. The traditional heat dissipation method has been unable to meet the demand, and the high-molecular polymer Kevlar 1414 has become the preferred material for preparing heat-conducting materials due to its light weight, low cost, good thermal stability and processability, but its intrinsic thermal conductivity is usually low. Filling high-thermal-conductivity inorganic fillers in the Kevlar 1414 matrix is an effective means to improve the thermal conductivity, which can provide excellent heat conduction performance and effectively reduce the working temperature of the equipment, thereby protecting the equipment from overheating damage.
[0003] From the perspective of heat conduction, the heat-conducting filler is the main heat-conducting medium and can form a heat transfer path. However, due to factors such as the large interfacial thermal resistance between the nanometer size and the polymer matrix and the disordered distribution in the matrix, a composite material with high thermal conductivity cannot be obtained. Therefore, reducing the interfacial thermal resistance between the heat-conducting filler and the matrix and realizing the ordered distribution of the heat-conducting filler in the matrix are the keys to improving the thermal conductivity. SUMMARY
[0004] One of the purposes of the present application is to provide a preparation method of a heat-conducting, insulating and electromagnetic shielding composite material,
[0005] The second purpose of the present application is to provide a heat-conducting, insulating and electromagnetic shielding composite material prepared by the above preparation method.
[0006] The third purpose of the present application is to provide the application of the above heat-conducting, insulating and electromagnetic shielding composite material.
[0007] To achieve the above purposes, the present application adopts the following technical solutions:
[0008] In the first aspect, the present application provides a preparation method of a heat-conducting, insulating and electromagnetic shielding composite material, which specifically comprises the following steps:
[0009] (1) placing Kevlar 1414 and carbon nanotube heat-conducting fillers in a concentrated sulfuric acid medium, and uniformly dispersing by means of ultrasonic and mechanical stirring;
[0010] (2) drying and hot-pressing the solution prepared in step (1) to form a composite heat-conducting film.
[0011] Preferably, in step (1), the Kevlar 1414 is a fully para-aramid copolymer fiber with a length of 6 mm and a diameter of 12 μm.
[0012] Preferably, in step (1), the carbon nanotubes are multi-walled carbon nanotubes with a diameter of 5-15 nm, a length of 10-30 μm, an aspect ratio in the range of 0.67-6, a purity of ≥ 99 wt%, and are single fillers without functional group modification.
[0013] Preferably, in step (1), the mass ratio of the Kevlar 1414 to the carbon nanotubes is 9:1-6:4.
[0014] Preferably, in step (2), the drying temperature is 40°C, and the hot-pressing pressure is 6.8 kPa.
[0015] Preferably, in step (2), the thickness of the composite heat-conductive film is 30-80 μm.
[0016] In a second aspect, the present application provides a heat-conductive and insulating electromagnetic shielding composite material prepared by the above preparation method.
[0017] The composite material comprises a matrix Kevlar 1414 and heat-conductive fillers multi-walled carbon nanotubes, wherein the heat-conductive fillers multi-walled carbon nanotubes are uniformly dispersed in the matrix Kevlar 1414.
[0018] In a third aspect, the present application also provides the use of the above heat-conductive and insulating electromagnetic shielding composite material in the heat dissipation of electronic devices under high-temperature extreme conditions.
[0019] Preferably, the electronic device is a COB lamp bead with a model number of 2828 and a color temperature of 6000 K, which generates heat of more than 180°C.
[0020] Carbon nanotubes have high thermal conductivity, ultra-high aspect ratio, ultra-high specific surface area, good compatibility and thermal stability, and are excellent carbon-based heat-conductive fillers. Therefore, uniform dispersion of carbon nanotubes in a Kevlar 1414 matrix and mechanical force ordered orientation through π-π anchoring between carbon nanotubes and Kevlar 1414 are expected to obtain a high-thermal-conductivity composite material, which realizes its application in the heat dissipation of high-temperature electronic devices. In addition, the composite material also has good insulation and excellent electromagnetic shielding properties.
[0021] Compared with the prior art, the present application has the following beneficial effects:
[0022] 1. The heat-conductive and insulating electromagnetic shielding material of the present application relies on the π-π anchoring between Kevlar 1414 and carbon nanotubes to enhance the interaction force at the interface between the matrix and the heat-conductive fillers, so that the heat-conductive composite film of the present application has high thermal conductivity, good processability, high-temperature resistance, flexibility, insulation, and electromagnetic shielding performance, and is suitable for the application requirements of heat dissipation of highly integrated and high-power electronic devices.
[0023] 2、The in-plane thermal conductivity of the heat-conducting insulating electromagnetic shielding material is 9.6 W / m·K-23.8 W / m·K, the electromagnetic shielding efficiency reaches 60% when 40wt% multi-walled carbon nanotubes are loaded, and the square resistance value reaches 4.51 KΩ / sq.
[0024] 3、The heat-conducting insulating electromagnetic shielding material can be applied to the heat dissipation of a COB lamp bead with a heat generation of more than 180℃ and a color temperature of 6000K.
[0025] 4、The heat-conducting insulating electromagnetic shielding material has good thermal stability, and the fastest decomposition rate is about 550℃. BRIEF DESCRIPTION OF DRAWINGS
[0026] Figure 1 is a flow chart and a physical diagram of the preparation of the heat-conducting insulating electromagnetic shielding material.
[0027] Figure 2 is an XRD diagram of the Kevlar and the composite material prepared in Examples 1-4.
[0028] Figure 3 is the SEM surface morphology and EDS element distribution of the Kevlar prepared in the comparative example.
[0029] Figure 4 is the SEM surface morphology and element distribution (a-d) of the composite material prepared in Examples 1-4, and the SEM cross-section morphology (e-h) of the composite material.
[0030] Figure 5 is the SEM surface morphology and element distribution of the Kevlar and the carbon nanotube coated by the Kevlar in the composite material prepared in Examples 1-4.
[0031] Figure 6 is an XPS diagram of the Kevlar and the composite material prepared in Examples 1-4.
[0032] Figure 7 is the thermal conductivity of the composite material prepared in Examples 1-4; wherein Figure 7 (a) is the in-plane thermal diffusivity of the composite material, Figure 7 (b) is the in-plane thermal conductivity of the composite material, Figure 7 (c) is the in-plane thermal conductivity increase range of the composite material, Figure 7 (d) is the in-plane thermal diffusivity of the composite material CNT-30% at different temperatures, Figure 7 (e) is the specific heat capacity of the composite material CNT-30% at different temperatures, Figure 7 (f) is the in-plane thermal conductivity of the composite material CNT-30% at different temperatures.
[0033] Figure 8is the electromagnetic shielding performance of the composite material prepared in Examples 1-4; wherein Figure 8 (a) is the electromagnetic shielding effectiveness of the composite material, Figure 8 (b) is the electromagnetic shielding efficiency of the composite material, Figure 8 (c) is the electromagnetic shielding SE A , SE R , SE T value of the composite material, Figure 8 (d) is the electromagnetic shielding vs. thermal conductivity graph of the composite material.
[0034] Figure 9 is the sheet resistance of the composite material prepared in Examples 1-4.
[0035] Figure 10 is the TGA graph of the composite material prepared in Examples 1-4.
[0036] Figure 11 is the mechanical property analysis of the composite material prepared in Examples 1-4.
[0037] Figure 12 is the thermal conductivity application of CNT-10% and CNT-40% of the composite material prepared in Examples 1-4; wherein Figure 12 (a) is the LED lamp heat dissipation infrared thermal image of CNT-10% and CNT-40% of the composite material, Figure 12 (b) is the LED lamp surface temperature vs. time curve of CNT-10% and CNT-40% of the composite material, Figure 12 (c) is the heat dissipation stability analysis of CNT-40% of the composite material as a thermal interface material. DETAILED DESCRIPTION
[0038] The present application will be further described in conjunction with the accompanying drawings and specific examples.
[0039] In the following examples, unless otherwise specified, the raw materials and reagents used are commercially available; Kevlar 1414 is a full para-aramid copolymer fiber produced by DuPont, with a length of 6 mm and a diameter of 12 μm; multi-walled carbon nanotubes are produced by Shanghai Adamas Reagent Co., Ltd., with a diameter of 5 nm to 15 nm, a length of 10 μm to 30 μm, an aspect ratio range of 0.67-6, and a purity of 99 wt%; the mass fraction of concentrated sulfuric acid is 98%.
[0040] Comparative Example
[0041] A thermally conductive and insulating electromagnetic shielding composite material (denoted as Kevlar), with pure Kevlar 1414 oriented in the plane of the composite film.
[0042] wherein the mass ratio of Kevlar 1414 is 100%.
[0043] According to the procedure shown in Figure 1 was prepared as follows:
[0044] Kevlar 1414 matrix (0.621 g) was placed in concentrated sulfuric acid (10 g) medium, with the aid of ultrasonic and mechanical stirring to uniform dispersion, by mechanical movement of glass rod between glass plate to drive Kevlar 1414 ordered orientation, after 40℃ drying, 6.8kPa hot pressing to form a composite heat conducting film.
[0045] Example 1
[0046] A kind of heat-conducting insulating electromagnetic shielding composite material (marked as CNT-10%), heat-conducting filler multi-walled carbon nanotube and Kevlar 1414 have a consistent orientation in the plane of composite film.
[0047] Wherein, the mass ratio of Kevlar 1414 and multi-walled carbon nanotube is 9:1, i.e. the mass fraction of multi-walled carbon nanotube is 10wt%.
[0048] According to the procedure shown in Figure 1 was prepared as follows:
[0049] Kevlar 1414 matrix (0.621 g) and carbon nanotube (0.069 g) heat-conducting filler were placed in concentrated sulfuric acid (10 g) medium, with the aid of ultrasonic and mechanical stirring to uniform dispersion, by mechanical movement of glass rod between glass plate to drive Kevlar 1414 and multi-walled carbon nanotube ordered orientation, after 40℃ drying, 6.8kPa hot pressing to form a composite heat conducting film.
[0050] Example 2
[0051] A kind of heat-conducting insulating electromagnetic shielding composite material (marked as CNT-20%), heat-conducting filler multi-walled carbon nanotube and Kevlar 1414 have a consistent orientation in the plane of composite film.
[0052] Wherein, the mass ratio of Kevlar 1414 and multi-walled carbon nanotube is 8:2, i.e. the mass fraction of multi-walled carbon nanotube is 20wt%.
[0053] The preparation method is the same as example 1.
[0054] Example 3
[0055] A kind of heat-conducting insulating electromagnetic shielding composite material (marked as CNT-30%), heat-conducting filler multi-walled carbon nanotube and Kevlar 1414 have a consistent orientation in the plane of composite film.
[0056] Wherein, the mass ratio of Kevlar 1414 and multi-walled carbon nanotube is 7:3, i.e. the mass fraction of multi-walled carbon nanotube is 30wt%.
[0057] The preparation method is the same as that of Example 1.
[0058] Example 4
[0059] A thermally conductive and insulating electromagnetic shielding composite material (denoted as CNT-40%) is prepared, in which the thermally conductive filler, multi-walled carbon nanotubes, and Kevlar 1414 have a uniform orientation in the plane of the composite film.
[0060] The mass ratio of Kevlar 1414 and multi-walled carbon nanotubes is 6:4, i.e., the mass fraction of multi-walled carbon nanotubes is 40 wt%.
[0061] The preparation method is the same as that of Example 1.
[0062] Figure 2 (b) is the XRD pattern of the thermally conductive and insulating electromagnetic shielding composite material CNT-10% to CNT-40% prepared in Examples 1-4, Figure 2 (a) is the XRD pattern of Kevlar film and multi-walled carbon nanotube powder. The XRD pattern of pure Kevlar film shows that there is a wide diffraction peak near ~20° corresponding to the (110) plane in its semi-crystalline structure. Multi-walled carbon nanotubes have a typical diffraction peak at about 20° corresponding to the (002) plane. In the composite sample, the peak of multi-walled carbon nanotubes is low in intensity at low loading, and the peak intensity increases with the increase of the loading amount.
[0063] Figure 3 is the SEM surface morphology and element distribution of the Kevlar film prepared in the comparative example. From the SEM image of the Kevlar film, it can be seen that the film surface formed by scraping is flat, and the elements C, N, and O are uniformly distributed on the material surface.
[0064] Figure 4 (a)- Figure 4 (d) is the SEM surface morphology and element distribution of the composite material prepared in Examples 1-4, it can be seen that the surface of the composite material is flat, and the elements C, N, and O are uniformly distributed, indicating that Kevlar 1414 and carbon nanotubes are uniformly distributed in the composite material system; Figure 4 (e)- Figure 4 (h) is the SEM cross-sectional morphology of the composite material prepared in Examples 1-4, it can be seen that the multi-walled carbon nanotubes are uniformly dispersed in the Kevlar 1414 matrix, and the multi-walled carbon nanotubes are oriented in the in-plane direction.
[0065] Figure 5 is the SEM surface morphology and element analysis of the Kevlar 1414 coated carbon nanotubes in the composite material prepared in Examples 1-4. It can be seen that the surface of the carbon nanotubes is uniformly coated with the Kevlar 1414 matrix.
[0066] Figure 6 XPS spectra of Kevlar, composite materials prepared in Examples 1-4. Figure 6 (a) are XPS spectra of Kevlar film, multi-walled carbon nanotube powder and CNT-20% composite film. Kevlar film shows characteristic peaks at 284.4 eV, 399.5 eV and 532.5 eV, corresponding to C1s, N 1s and O1s, respectively. Multi-walled carbon nanotubes show characteristic peaks of O1s and C1s at 532.5 eV and 284.4 eV, respectively. The O characteristic peak may be due to the adsorption of oxygen or water molecules in the environment during the preparation, storage or handling of multi-walled carbon nanotubes. CNT-20% shows characteristic peaks of C1s, N 1s and O1s at 285 eV, 400 eV and 532.5 eV, respectively. In addition, the C1s binding energy of C-N of CNT-20% film is 286.37 eV, which is higher than that of Kevlar. These results indicate that the chemical environment of C=O and N-H has changed, further confirming the formation of π-π stacking interactions between Kevlar 1414 and multi-walled carbon nanotubes in the composite material.
[0067] Figure 7 Thermal conductivity of the composite materials prepared in Examples 1-4. Among them Figure 7 (a) are the in-plane thermal diffusivity of composite materials CNT-10%, CNT-20%, CNT-30%, CNT-40%. Figure 7 (b) are the in-plane thermal conductivity of composite materials CNT-10%, CNT-20%, CNT-30%, CNT-40%. Figure 7 (c) are the in-plane thermal conductivity increase of composite materials CNT-10%, CNT-20%, CNT-30%, CNT-40%. Figure 7 (d) are the in-plane thermal diffusivity of composite material CNT-30% at different temperatures. Figure 7 (e) are the specific heat capacity of composite material CNT-30% at different temperatures. Figure 7 (f) are the in-plane thermal conductivity of composite material CNT-30% at different temperatures. Figure 7 The in-plane thermal diffusivity of CNT-10%, CNT-20%, CNT-30%, CNT-40% in (a) are 4.48, 7.84, 11.08, 13.37 mm 2 / s, respectively. Figure 7 The in-plane thermal conductivity of CNT-10%, CNT-20%, CNT-30%, CNT-40% in (b) are 9.6, 14.2, 20.2, 23.8 W / m·K, respectively. Figure 7(c) in which the in-plane thermal conductivity of the composite materials CNT-10%, CNT-20%, CNT-30%, CNT-40% is increased by 296%, 516%, 734% and 882% compared with pure Kevlar film. Considering the interface interaction and synergistic orientation of Kevlar 1414 and multi-walled carbon nanotubes, the composite film should exhibit good thermal conductivity in the in-plane direction, and the thermal conductivity gradually increases with the increase of the load of multi-walled carbon nanotubes. Figure 8 (d) in which the in-plane thermal diffusivity of the composite material CNT-30% at 25, 100, 150, 200, 250°C is 11.08, 11.14, 11.33, 11.76, 12.80 mm 2 / s, the thermal diffusivity changes little with temperature, showing good stability. Figure 8 (e) in which the specific heat capacity of the composite material CNT-30% at 25, 100, 150, 200, 250°C is 1.34, 1.38, 1.49, 1.50, 1.57 KJ / kg·K. Figure 8 (f) in which the thermal conductivity of CNT-30% at 25, 100, 150, 200, 250°C is 20.2, 20.9, 23.0, 24.0, 27.3 W / m·K, and the thermal conductivity of CNT-30% composite film shows an upward trend with the increase of temperature.
[0068] Figure 8 is the electromagnetic shielding performance of the composite materials prepared in Examples 1-4. Among them Figure 8 (a) is the electromagnetic shielding effectiveness of the composite materials CNT-10%, CNT-20%, CNT-30%, CNT-40%. Figure 8 (b) is the electromagnetic shielding efficiency of the composite materials CNT-10%, CNT-20%, CNT-30%, CNT-40%. Figure 8 (c) is the electromagnetic shielding SE A , SE R , SE T value of the composite materials CNT-10%, CNT-20%, CNT-30%, CNT-40%. Figure 8 (d) is the electromagnetic shielding and thermal conductivity relationship diagram of the composite materials CNT-10%, CNT-20%, CNT-30%, CNT-40%. From Figure 9 it can be seen that the electromagnetic shielding effectiveness of the composite material gradually increases with the increase of the load of multi-walled carbon nanotubes, and the electromagnetic shielding efficiency also shows the same change trend. From Figure 10 (c) SE A , SE R , SE T value can be seen that the SE A value of the composite material is higher than that ofR The values show that the composite material is an electromagnetic shielding material mainly in the absorption type. From the Figure 11 (d) It can be concluded that the electromagnetic shielding and thermal conductivity performance are simultaneously enhanced with the increase of carbon tube loading.
[0069] Figure 12 The sheet resistance of the composite materials CNT-20%, CNT-30%, CNT-40% prepared in Examples 1-4 is shown. The Kevlar 1414 matrix itself is insulating, and with the increase of carbon tube loading, the sheet resistance value gradually decreases, but it has reached the KΩ level, which still does not belong to the conductor order of magnitude.
[0070] Figure 12 The TGA graph of the composite materials CNT-10%, CNT-20%, CNT-30%, CNT-40% prepared in Examples 1-4 is shown. From the graph, it can be seen that the fastest decomposition rate value is about 550°C, which shows that the composite material has good thermal stability.
[0071] Figure 12 The mechanical property analysis of the composite materials CNT-10%, CNT-20%, CNT-30%, CNT-40% prepared in Examples 1-4 is shown. From the graph, it can be seen that the composite materials all show good mechanical properties.
[0072] Application 1: The composite thermal conductive films CNT-10% and CNT-40% prepared in Examples 1 and 4 are used as thermal interface materials in the heat management application of LED lamp heat dissipation process. Device: 20W COB LED lamp bead (model 2828), color temperature 6000K. The composite material CNT-10% has a thermal conductivity of 9.6W / m·K, and the composite material CNT-40% has a thermal conductivity of 23.8W / m·K. Extreme high temperature application: place CNT-10% and CNT-40% between the LED lamp and the aluminum heat sink, respectively. The steady-state average temperature of the LED lamp bead with CNT-10% and CNT-40% as thermal interface material is 202°C and 180°C after lighting for 150s, and the LED lamp surface temperature remains stable after running for 650s, which shows that CNT-10% and CNT-40% as thermal interface material have stable heat dissipation performance and can be applied to extreme high temperature conditions above 180°C.
[0073] Figure 12 The thermal conductivity application of the composite materials CNT-10% and CNT-40% prepared in Examples 1-4 is shown. Among them Figure 12 (a) is the infrared thermal image of the LED lamp heat dissipation of the composite materials CNT-10% and CNT-40%. Figure 12 (b) is the LED lamp surface temperature-time curve of the composite materials CNT-10% and CNT-40%. Figure 12(c) is the heat dissipation stability analysis of the composite CNT-40% as thermal interface material. From Figure 12 (a) can be seen directly with the extension of time, the LED lamp surface temperature of CNT-10% as thermal interface material is higher than that of CNT-40% as thermal interface material, which shows that the heat dissipation performance of CNT-40% is higher than that of CNT-10%; in addition (b) records the surface temperature during the LED heating process, and from the data, it can be seen that the LED lamp surface temperature of CNT-40% as thermal interface material is 23℃ lower than that of CNT-10% as thermal interface material. From (c) can be seen that the LED bulb surface temperature is still stable after 25 cycles, which shows that the composite as thermal interface material has good stability when dissipating heat.
Claims
1. A method for preparing a thermally conductive, insulating, and electromagnetic shielding composite material, characterized in that: The specific steps include: (1) placing the Kevlar 1414 matrix and the carbon nanotube thermal conductive filler in a concentrated sulfuric acid medium and stirring them with ultrasound and mechanical stirring until they are uniformly dispersed; (2) The solution obtained in step (1) is dried and hot-pressed to form a composite thermal conductive film.
2. The method for preparing a thermally conductive, insulating, and electromagnetic shielding composite material according to claim 1, wherein: In step (1), the Kevlar 1414 is a fully para-aramid copolymer fiber with a length of 6 mm and a diameter of 12 μm.
3. The method for preparing a thermally conductive insulating electromagnetic shielding material according to claim 1, characterized in that: In step (1), the carbon nanotubes are multi-walled carbon nanotubes with a diameter of 5 to 15 nm, a length of 10 to 30 μm, an aspect ratio of 0.67 to 6, a purity of ≥99 wt%, and a single filler without functional group modification.
4. The method for preparing a thermally conductive insulating electromagnetic shielding material according to claim 1, characterized in that: In step (1), the mass ratio of the Kevlar 1414 to the carbon nanotubes is 9:1 to 6:
4.
5. The method for preparing a thermally conductive insulating electromagnetic shielding material according to claim 1, characterized in that: In step (2), the drying temperature is 40° C. and the hot pressing pressure is 6.8 kPa.
6. The method for preparing a thermally conductive insulating electromagnetic shielding material according to claim 1, characterized in that: In step (2), the thickness of the composite thermally conductive film is between 30-80 μm.
7. A thermally conductive, insulating, and electromagnetic shielding composite material obtained by the preparation method according to any one of claims 1 to 6.
8. Use of the thermally conductive, insulating, and electromagnetic shielding composite material according to claim 7 in heat dissipation of high-temperature electronic devices.
9. The use according to claim 8, characterized in that The electronic device is a COB lamp bead with a heat output of more than 180°C, model 2828, and a color temperature of 6000K.
